Transcatheter Valve Replacement: New concepts for Microsurgery inside the Heart. Issue 1 (January 2013) - Brecht, Ralf; Friedrich, Maximilian; Heinisch, Paul Philipp; Plonien, Katharina; Akra, Bassil; Hagl, Christian; Khoynezhad, Ali; Lutter, Georg; Bombien, René
Objective: Transcatheter aortic valve implantation gained clinical relevance with an impressive and peerless power; however, the procedure induces unsolved complications such as paravalvular leakage, occlusion of coronary ostia, and vascular complications. The safe removal of bulky calcified valves will improve the outcome, well known through the open surgical procedure. In this article, a new stapler-based resection and implantation device as well as a new approach for valve isolation during normal heart cycle without extracorporeal circulation will be analyzed. Methods: First, a novel stapler-based instrument for transapical aortic valve replacement [removal and implantation; stapler-based aortic valve replacement (StapAVR)] was constructed and analyzed in an aortic debris model. Artificial aortic valves (N = 20), containing fluorescent granules to simulate the calcification, were placed into an aortic model in anatomical supine position (DP) and right-sided lateral position (RP). With the StapAVR, resection before implantation was performed in a water-filled basin. Black light was used for debris visualization. The procedures have been digitally recorded and analyzed due to procedural times, and the debris amount in thoracic side branches. Second, an enhanced prototype of the pulmonary valve isolation chamber (PVIC) was analyzed in porcine in vitro (n = 10) and in vivo models (n = 1). This PVIC contains a microaxial pump (Impella; Abiomed, Aachen, Germany) in the central bypass channel. It was deployed through the right ventricular wall. Once the PVIC was in place, the pump was started before isolating the valve. The complete hemodynamic monitoring was digitally recorded. Results: The deployment of the StapAVR in the correct position and the valve resection time took a mean (SD) of 95.8 (19) seconds in DP and 90.1 (18) seconds in RP. Fluorescent debris was found: in the left coronary artery, 22% in DP and 7% in RP; in the ascending aorta, 0% in DP and 11% in RP; in the aortic bulbous, 5% in DP and 10% in RP; in the left ventricle, 8% in DP and 14% in RP; in the brachiocephalic trunk, 4% in DP and 9% in RP; and in the descending aorta, 46% in DP and 1% in RP. Consecutive valved stent implantation was performed without complications. The PVIC deployment time in vivo was 5 minutes, replacements included. The total valve isolation time was 21 minutes, with a mean (SD) bypass flow of 2.1 (0.4) L/min. The oxygen saturation showed a median of 91% (range, 83%–97%), and the median arterial blood pressure was 69 mm Hg (systolic; range, 47–120 mm Hg) and 40mm Hg (diastolic; range, 32–56 mm Hg) without the use of inotropes or vasopressors. Electrocardiogram confirmed sinus rhythm during isolation. Conclusions: The resection of the artificial valves followed by valved stent implantation was possible with the StapAVR. In vivo, the procedure will be carried out under rapid pacing and sudden vacuum; however, the results of this in vitro debris model underline the need for isolation or filter devices during transcatheter aortic valve implantation to avoid embolization. Secondly, the use of the pump-advanced PVIC showed stable heart function for 21 minutes under isolated pulmonary valve conditions. This time will be adequate to remove bulky calcifications and to implant a valved stent. Improvements of both prototypes are ongoing. Nevertheless, the presented concepts showed promising application possibilities in the future.